Is Reconsolidation a General Property of Memory? - Kim, Gayoung; Kwon, Minjae; Kang, Wonjun; Lee, Sue-Hyun (Frontiers in Human Neuroscience, 2021)
Memory reconsolidation holds great hope for memory modification approaches and clinical treatments of mental disorders associated with maladaptive memories. However, it remains controversial as to whether reconsolidation is a general property of all types of memory. Especially, discrepancies have been reported in research focusing on whether declarative memory undergoes reconsolidation, and whether old memories can be reorganized after retrieval. Here, we discuss how these inconsistent results can be reconciled and what information we need to uncover for the general use of reconsolidation.